INGLIZ TILINI O‘QITISH JARAYONIDA TALABALARNING IJTIMOIY-MADANIY KOMPETENSIYALARINI RIVOJLANTIRISH - Abdusattarov Mavlon Sherali o‘g‘li, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
Nowadays the time itself requires the use of modern and innovative methods in teaching the English language. As a consequence, in language teaching it involves developing several competencies. Competency is a complex of knowledge, skills and abilities directed to activity in using the language. This article focuses on the importance of developing students’ socio-cultural competence, targets and intended consequences.